THE EVALUATION OF STREPTOKINAZ REZISTANCE, A FIBRINOLYTIC AGENT IN HIGH RISK PROFILE FOR CORONARY ARTERY DISEASE LIVING UPPER FIRAT REGION - Bulut, Musa; Baydas, Adil; Kobat, Mehmet Ali; Yavuzkir, Mustafa; Dagli, Necati; Balin, Mehmet; Karaca, Ilgin (Elsevier Ireland Ltd, 2010)
[Abstract Not Available]